Effects of Collaboration Care Model on the Quality of Life in Patients after Coronary Angioplasty: A Randomized Controlled Clinical Trial - Parastoo Rezapoor; Mohsen Shahriari; Hamid Sanei; Mahin Moeini (Shiraz University of Medical Sciences, 2017)
Background: Coronary artery diseases and therapies such as coronary angioplasty would lead to changes in the quality of life in patients. The aim of this study was to determine the effects of collaborative care model on the quality of life in patients after coronary angioplasty. Methods: This randomized controlled clinical trial was conducted in Isfahan, Iran during 2015. In this study, 50 samples were selected by simple sampling and randomly allocated into two equal groups of intervention and control. Collaborative care model was performed in the intervention group for 3 months. Data were collected using quality of life (SF-36) questionnaire which includes 36 questions on physical and psychological dimensions and was completed before and one month after the intervention in both groups. Data were analyzed using descriptive and analytical statistics and by independent t- test, paired t test, Chi square and Mann-Whitney tests through SPSS 18. Results: After the intervention, the mean score of quality of life in the intervention group was significantly higher than the control group (P<0.05). The results of independent t-test showed a significant difference between both groups regarding the mean of changes in the score of quality of life and its dimensions in patients undergoing coronary angioplasty 3 months after the intervention (P<0.001). Conclusion: Results revealed that patients who had been cared based on collaborative care model had better scores of quality of life in all the physical, mental and social dimensions than the control group. Therefore, using this model for taking care of patients after coronary angioplasty is recommended.